Problem 8

  • # mod5 mod7
    0 0 0
    1 1 1
    2 2 2
    3 3 3
    4 4 4
    5 0 5
    6 1 6
    7 2 0
    8 3 1
    9 4 2
    10 0 3
    11 1 4
    12 2 5
    13 3 6
    14 4 0
    15 0 1
    16 1 2
    17 2 3
    18 3 4
    19 4 5
    20 0 6
    21 1 0
    22 2 1
    23 3 2
    24 4 3
    25 0 4
    26 1 5
    27 2 6
    28 3 0
    29 4 1
    30 0 2
    31 1 3
    32 2 4
    33 3 5
    34 4 6
    35 0 0
    36 1 1
  • For this to be true, \(x\) and \(y\) must be relatively prime. From this, we can observe a pattern that forms where there are unique pairs for (x,y) until the \(x*yth\) pair (or index). In our example, \(x=5\), \(y=7\), and it will have unique pairs until the pattern repeats on the \(35th\) index (which is x*y).

  • Since x and y are prime the \(gcd(x,y) = 1\).

    Using Bezout’s identity we know \(y(y^{-1}modx) + x(x^{-1}mody)=1\)

    Then you can multiply both sides by \(q\).

    \(qy(y^{-1}modx) + qx(x^{-1}mody)=q\)

    Now if you \(modx\) both sides, you get:

    \(qy(y^{-1}modx)modx + qx(x^{-1}mody)modx=qmodx\)

    so

    \(qy(y^{-1}modx)modx = 1*q\)

    \(qx(x^{-1}mody)modx = 0\)

    Therefore: \(qy(y^{-1}modx)modx + qx(x^{-1}mody)modx = qmodx = m\)

    The coefficient for the \(y(y^{-1}modx)\) term is \(m\). Then if you take \(mody\) of the function, you get:

    \(qy(y^{-1}modx)mody + qx(x^{-1}mody)mody = qmody = n\).

    So the coefficient of the \(x(x^{-1}mody)\) term is \(n\).

    Then we have \(my(y^{-1}modx) + nx(x^{-1}mody) = q\). But Bezout’s identity says this will only work for specific \(y^{-1}modx\) and \(x^{-1}mody\). So to get this formula to work for all \(y^{-1}modx\) and \(x^{-1}mody\) we need to add a \(modxy\) term.

    So the final formula is \(q=[my(y^{-1}modx) + nx(x^{-1}mody)]modxy\)

  • In the case where there are three primes \(x,y,z\), the properties from above still hold. There will be unique pairs until the \(x*y*zth\) index.